2015
DOI: 10.1123/jpah.2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Family Cohesion and Moderate-to-Vigorous Physical Activity Among Mexican Origin Adolescents: A Longitudinal Perspective

Abstract: Background Existing racial/ethnic disparities in physical activity during childhood increase Hispanics' risk of developing chronic diseases, which serves to increase health disparities. This study examined associations of family cohesion and conflict with self-reported moderate-to-vigorous physical activity (MVPA), controlling for psychosocial covariates such as subjective social status, anxiety, and sensation-seeking. Methods 1000 Mexican origin adolescents reported their MVPA levels approximately 2 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…This was also confirmed by Ornelas et al who found positive associations of family cohesion, parent–child communication, and parental engagement in physical activity with PAL [ 57 ]. Prospective research by Bigman et al showed a correlation between family cohesion and conflict with PALs among Mexican adolescents [ 58 ]. Adolescents who reported high family cohesion had a 32% greater likelihood of having a higher PAL than adolescents who reported lower family cohesion [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also confirmed by Ornelas et al who found positive associations of family cohesion, parent–child communication, and parental engagement in physical activity with PAL [ 57 ]. Prospective research by Bigman et al showed a correlation between family cohesion and conflict with PALs among Mexican adolescents [ 58 ]. Adolescents who reported high family cohesion had a 32% greater likelihood of having a higher PAL than adolescents who reported lower family cohesion [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective research by Bigman et al showed a correlation between family cohesion and conflict with PALs among Mexican adolescents [ 58 ]. Adolescents who reported high family cohesion had a 32% greater likelihood of having a higher PAL than adolescents who reported lower family cohesion [ 58 ]. In contrast, a significant correlation between family conflict and PAL was not found [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…55 Our study and the only 2 prior studies that (to our knowledge) have examined associations between Latino parent/caregiver and youth physical activity levels identified moderate to strong associations. 34,35 From a sociocultural perspective, behavioral aggregation could be stronger within Latino families due to traditionally higher family cohesion and valuation, 56 which might lead families to share activities and support mutual interests. Strong family ties could be a resource for interventions addressing obesity-related behaviors in Latino youth and physical activity and sedentary interventions including parents/caregivers may be particularly effective.…”
Section: Discussionmentioning
confidence: 99%
“…The need for the family to be involved in order to promote of healthy lifestyles is evident since the very moment where the family beliefs on what healthy means establishes a firm foundation for the young adults to consolidate their path to achieve a better health. Some components of family functioning, such as cohesion, have proved to be linked to lifestyles in young people as they encourage physical activity [13] and protect against alcohol [15,16] and tobacco consumption [19]. However, this evidence has not been reported in Latinos and the information available in groups of women is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression symptoms during adolescence are associated with unhealthy lifestyles [12]. Adequate levels of moderate to vigorous physical activity in young women are associated with family cohesion [13], although another study in Mexican adolescents found no association between family structure, dynamics, physical activity and physical inactivity [14].…”
mentioning
confidence: 99%